2015
DOI: 10.1063/1.4935564
|View full text |Cite
|
Sign up to set email alerts
|

Elastic behavior of carbon nanocoils: A molecular dynamics study

Abstract: Elastic behavior of carbon nanocoils is investigated through molecular dynamics simulations. In particular, spring constants of various nanocoils are derived. To do so, first a geometric model is prepared with the aid of finite element mesh generator. Then applying AIREBO potential, the model is simulated under tensile loading. Using the obtained deformation data, the spring constant is calculated. In order to study the effect of structural parameters, change of elastic properties with helix diameter as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Activation by an AMF cycloheptriene which alters the chemical properties. [12] CCOIL's helical structure makes it suitable as an electromagnetic wave absorber and for inducing currents through inductive electromotive forces. [11e,13] The high thermal conductivity of allotropes can provide better heat conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Activation by an AMF cycloheptriene which alters the chemical properties. [12] CCOIL's helical structure makes it suitable as an electromagnetic wave absorber and for inducing currents through inductive electromotive forces. [11e,13] The high thermal conductivity of allotropes can provide better heat conduction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] Zaeri and Ziaei‐Rad found that the spring constants for a series of coiled CNTs with the same CNTs diameter decreased with the increase in the diameter of coil via molecular dynamic (MD) simulations. [ 30 ] Feng et al found that the tensile behaviors of small‐radius coiled CNTs with more turns were similar to those of mechanical springs while large‐radius coiled CNTs with more turns could not be stretched uniformly along their axial direction. [ 31 ] Sharifian found that the stretching of the coiled CNTs increased with the increase of inner radius.…”
Section: Introductionmentioning
confidence: 99%
“…In mechanics, a large body of both pioneering experimental and theoretical works have been conducted to reveal the mechanical characteristics of single-helical carbon coils (SHCNCs). 17,[19][20][21][22][23][24][25][26][27][28][29][30][31] It has been reported that tensile mechanical properties of SHCNCs are strongly relied on the geometrical parameters. [30][31][32][33] Experimental measurements via atomic force microscopy (AFM) and manipulator-equipped scan electron microscopy (SEM) techniques demonstrated that depending on the coil radius and coil pitch, Young's modulus of SHCNCs varies from 0.04 to 0.9 TPa, 17,19,21 and strain-induced buckling instability was identified in multi-walled SHCNCs subjected to compression.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Experimental measurements via atomic force microscopy (AFM) and manipulator-equipped scan electron microscopy (SEM) techniques demonstrated that depending on the coil radius and coil pitch, Young's modulus of SHCNCs varies from 0.04 to 0.9 TPa, 17,19,21 and strain-induced buckling instability was identified in multi-walled SHCNCs subjected to compression. 20 Theoretically, Young's modulus of sparse SHCNCs falls in the range from around 0.003 to 0.02 TPa, 23,25,[28][29][30][31]34 also relying on the dimensionalities. Striking discrepancies in tensile stiffnesses between experimental and theoretical data mainly attribute to the significantly different dimensionalities in SHCNC samples.…”
Section: Introductionmentioning
confidence: 99%